PENGARUH KUALITAS SISTEM DAN KUALITAS INFORMASI TERHADAP KEPUASAN PENGGUNA APLIKASI PELAYANAN PELANGGAN TERPUSAT (AP2T) PT PLN (PERSERO) WILAYAH KALIMANTAN TENGAH DAN KALIMANTAN SELATAN AREA BARABAI - Ferra Maryana; Rakhmi Ridhawati; Tuti Arum Sayekti (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2018)
Abstract, This study aimed to give empirical evidences about the effect of system and information quality to user satification of AP2DT PT PLN Persero, Tbk in Barabai Area. The independent variable was system quality and information quality. The dependent variable was user satisfication. The population in this study was 150 employees of PT PLN Persero, Tbk in Barabai Area. The data collected from the output of questionnaires which gived to the respondents. The samples technique used purposive sampling with 38 employees as respondent. The study gived empirical evidences that system quality and information quality had effect to user satification.